A theoretical analysis of the potential effect of negative pressure in wood drying based on a CT-scanner study. Issue 14 (1st November 2022) - Riley, Steve; Harrington, Jonathan; Elustondo, Diego
Abstract: A CT-scanner was used to scan 25 mm thick radiata pine boards during drying at 90 °C dry-bulb and 60 °C wet-bulb temperatures. Twenty transverse sections spaced by 10 mm along the length of the boards were CT-scanned six times during drying, and an elastic image registration technique was used to transform the CT-scanned images into moisture content profiles. The resulting images suggested that moisture content distributions did not always resemble diffusion-like moisture transfer mechanism, so common assumptions based on moisture content gradients as the main driving force for wood drying may not always be enough to explain the development of wet and dry zones coexisting below and above fiber saturation point. This paper discusses these findings based on both experimental CT-scanner data and the theory of water potential, which it is argued provides a more complete description of driving forces in wood drying.